The Neuropsychoanalytic Approach: Using Neuroscience as the Basic Science of Psychoanalysis - Johnson, Brian; Flores Mosri, Daniela (Frontiers in Psychology, 2016)
NEUROSCIENCE AS THE BASIC SCIENCE OF PSYCHOANALYSIS Neuroscience was the basic science behind Freud’s psychoanalytic theory and technique. He worked as a neurologist for 20 years before being aware that a new approach to understand complex diseases, namely the hysterias, was needed. Solms coined the term neuropsychoanalysis to affirm that neuroscience still belongs in psychoanalysis. The neuropsychoanalytic field has continued Freud’s original ideas as stated in 1895. Developments in psychoanalysis that have been created or revised by the neuropsychoanalysis movement include pain/relatedness/opioids, drive, structural model, dreams, cathexis, and dynamic unconscious. Neuroscience has contributed to the development of new psychoanalytic theory, such as Bazan’s (2011) description of anxiety driven by unconscious intentions or “phantoms.” Results of adopting the “dual aspect monism” approach of idiographic psychoanalytic clinical observation combined with nomothetic investigation of related human phenomena include clarification and revision of theory, restoration of the scientific base of psychoanalysis, and improvement of clinical treatments. By imbricating psychoanalytic thinking with neuroscience, psychoanalysts are also positioned to make contributions to neuroscience research. Freud’s original Project for a Scientific Psychology/Psychology for Neurologists can be carried forward in a way that moves psychoanalysis into the 21st century as a core contemporary science (Kandel 1999). Neuroscience as the basic science of psychoanalysis both improves the field, and enhances its scientific and cultural status.